Hematopoietic stem cell discovery: unveiling the historical and future perspective of colony-forming units assay - Nur Afizah Yusoff; Zariyantey Abd Hamid; Siti Balkis Budin; Izatus Shima Taib (PeerJ)
Stem cells are special cells with the distinctive capability to self-renew, forming a new pool of undifferentiated stem cells. They are also able to differentiate into lineage-specific cell types that are specialized and matured. Thus, stem cells are considered as the building blocks of tissues and organs in which they reside. Among the many types of stem cells, hematopoietic stem cells (HSCs) are the most studied adult stem cells and are considered as a promising source of cells for applications in the clinical and basic sciences. Historically, research on HSCs was initiated in the 1940s, where in a groundbreaking experiment, intravenously injected bone marrow (BM) cells prevented the death of irradiated mice by restoring blood cell production. Since then, HSCs have been studied and utilized in medical therapies and research for over several decades. Over time, more sophisticated tools have been developed to evaluate the behaviour of specifically purified subsets of hematopoietic cells that have the capacity to produce blood cells. One of the established tools is the colony-forming units (CFUs) assay. This assay facilitates the identification, enumeration, and analysis of colonies formed by differentiated hematopoietic stem and progenitor cells (HSPCs) from myeloid, erythroid and lymphoid lineages. Hence, the CFUs assay is a fundamental in vitro platform that allows functional studies on the lineage potential of an individual HSPCs. The outcomes of such studies are crucial in providing critical insights into hematopoiesis. In this review, we explore the fundamental discoveries concerning the CFUs assay by covering the following aspects: (i) the historical overview of the CFUs assay for the study of clonal hematopoiesis involving multilineage potential of HSPCs, (ii) its use in various experimental models comprising humans, mice/rodents, zebrafish and induced pluripotent stem cells (iPSCs) and (iii) research gaps and future direction concerning the role of CFUs assay in clinical and basic sciences. Overall, the CFUs assay confers a transformative platform for a better understanding of HSPCs biology in governing hematopoiesis.